Crystallization and preliminary X-ray analysis of the core particle of bluetongue virus. - Burroughs, J; Grimes, J; Mertens, P; Stuart, D (1995)
Core particles of bluetongue virus serotype 1 (South Africa) have been crystallized. The crystals, which grow up to 0.8 mm in diameter, belong to a primitive orthorhombic space group and have point group symmetry 222. The unit cell dimensions are 754 x 796 x 823 A3 and the crystallographic asymmetric unit contains one-half of a core particle. The best crystals diffract strongly to 4.8 A Bragg spacings, which is the maximum resolution to which we can measure data with the detectors available, suggesting that useful diffraction extends well beyond this. Core particles of serotype 10 have also been crystallized but the crystals have yet to be analyzed by X-ray diffraction.